1996
DOI: 10.1074/jbc.271.26.15303
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor α Inhibits Glutamate Uptake by Primary Human Astrocytes

Abstract: Human immunodeficiency virus (HIV) infection is commonly associated with neurological disease that occurs in the apparent absence of extensive infection of brain cells by HIV, suggesting that indirect mechanisms account for neuropathogenesis in the CNS, perhaps including changes in the normal neuroprotective functions of astrocytes. To test this hypothesis, we examined the effect of the pro-inflammatory cytokine, tumor necrosis factor alpha (TNFalpha), produced by HIV-1-infected macrophages and microglia, on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
181
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 303 publications
(187 citation statements)
references
References 28 publications
4
181
1
1
Order By: Relevance
“…If an excitotoxic mechanism is operating in HIV-1 infection, note that PAF is known to enhance excitatory transmission [27]. TNF-␣ [28] and arachidonic acid [29] block the crucial high-affinity glutamate uptake of astrocytes at synaptic clefts. Restricted HIV infection of astrocytes and over-expression of regulatory proteins such as tat or nef may further compromise vital astrocyte functions [30].…”
Section: Excitotoxic Injury In the Developing Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…If an excitotoxic mechanism is operating in HIV-1 infection, note that PAF is known to enhance excitatory transmission [27]. TNF-␣ [28] and arachidonic acid [29] block the crucial high-affinity glutamate uptake of astrocytes at synaptic clefts. Restricted HIV infection of astrocytes and over-expression of regulatory proteins such as tat or nef may further compromise vital astrocyte functions [30].…”
Section: Excitotoxic Injury In the Developing Nervous Systemmentioning
confidence: 99%
“…Attempting to reduce levels of TNF-␣ in brain would be a cornerstone of therapy because Tat can up-regulate TNF-␣ production in glial cells [51,52] and TNF-␣ in turn can induce neuronal apoptosis by a mechanism that is independent of NF-B activation but involves activation of non-NMDA receptors [21,32], as well as reduce glutamate uptake [28]. Agents are presently available to decrease TNF-␣ production at the transcriptional level and to bind to TNF-␣ (soluble receptor fragments), but delivery across the blood-brain barrier may limit their efficacy.…”
Section: Therapeutic Strategies For Hiv-1 Infection In the Developingmentioning
confidence: 99%
“…The excitatory amino acid transporter 2 (EAAT2) prevents glutamate toxicity by removing excess glutamate from the synaptic cleft. Treatment with TNF-a down-regulates EAAT2 mRNA and protein and also inhibits EAAT2-Prom activity in primary human fetal astrocytes (18,19) The primary pathway by which TNF-a suppresses EAAT2 expression is by activating NF-nB (19,20) that binds to the EAAT2 promoter and inhibits its activity. Interestingly, ectopic expression of AEG-1 also inhibits EAAT2 promoter activity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a clear connection between improper uptake capacity and CNS damage. Products of HIV infection, gp120 and TNF-α, inhibit glutamate uptake by astrocytes (148,149). Compounding these effects, HIV-1 has been shown to downregulate glutamate transporter EAAT2, causing disruptions in glutamate uptake (149).…”
Section: Impairment Of Astrocytes In Hadmentioning
confidence: 99%
“…Further, G-protein linked mGlu receptors may cause increased intracellular Ca 2+ , leading to glutamate release from astrocytes (150). Astrocytic release of glutamate has been shown to be stimulated by arachidonic acid, TNF-α, and CXCL12 (50,148,151). In addition, numerous studies have indicated a potential for the reversal of glutamate uptake, causing further glutamate dumping (152,153).…”
Section: Impairment Of Astrocytes In Hadmentioning
confidence: 99%